Prime toeic listening : (Tổng hợp Thành phố Hồ Chí Minh, 2014)
Contents: Part 1: Photograph Descriptions Chapter 1: IntroductionChapter 2: photos focusing on actionsChapter 3: photos focusing on Objects/ scenes/ settingsPart 2: Questions & ResponsesChapter 1: IntroductionChapter 2: Questions TypesPart 3 & 4 : Short Conversations/ Short Talks